Tinjauan Pengelolaan Pasar Rakyat Jambangan di Surabaya: Implementasi Kebijakan Menurut Charles O. Jones - Pratama Putra, Yogi; Hertati, Diana (Jurnal Administrasi Politik dan Sosial, 2024)
In terms of national development, especially in the trade aspect, physical development is very necessary, one of which is the development and maintenance of markets. This is because many job opportunities are opening up in the informal sector. So it can reduce the unemployment rate in an area. In efforts to develop or maintain markets, a law is needed that regulates market management. The Jambangan people's market is one of the markets assisted by the Surabaya City Cooperatives, SMEs and Trade Department, although the market is relatively new, several problems have arisen from several aspects. So this research aims to look at the implementation of people's market management policies at the Jambangan people's market using policy implementation theory according to Charles O. Jones. The research uses descriptive research methods with a qualitative approach. The results of this research are that the Department of Cooperatives, SMEs and Trade of the City of Surabaya has not been optimal in managing the vase public market, seen from the fact that there are still problems in terms of the quality of facilities as well as supervision or guidance that is not evenly distributed and optimal.